14-3-3 Proteins in Plant Hormone Signaling: Doing Several Things at Once - Camoni, Lorenzo; Visconti, Sabina; Aducci, Patrizia; Marra, Mauro (Frontiers in Plant Science, 2018)
In this review we highlight the advances achieved in the investigation of the role of 14-3-3 proteins in hormone signaling, biosynthesis and transport. 14-3-3 proteins are a family of conserved molecules that target a number of protein clients through their ability to recognize well-defined phosphorylated motifs. As a result, they regulate several cellular processes, ranging from metabolism to transport, growth, development and stress response. High-throughput proteomic data and two-hybrid screen demonstrate that 14-3-3 proteins physically interact with many protein clients involved in the biosynthesis or signaling pathways of the main plant hormones, while increasing functional evidence indicates that 14-3-3-target interactions play pivotal regulatory roles. These advances provide a framework of our understanding of plant hormone action, suggesting that 14-3-3 proteins act as hubs of a cellular web encompassing different signaling pathways, transducing and integrating diverse hormone signals in the regulation of physiological processes.